Binding energy of the ground and first few excited states of a shallow-donor impurity in rectangular-cross-sectional area GaAs quantum-well wires under applied electric field (1998)
ABSTRACT: Using a variational approach within the effective mass approximation we calculate the binding energy of the ground and some excited donor impurity states in quantum-well wires with rectangular and cylindrical transversal sections under the action of applied electric fields. We study the binding energy as a function of the geometry of the system, the applied electric field as well as the impurity position inside the structure. We found that the presence of the electric field breaks down the degeneracy of states for impurities symmetrically positioned within the structure, and that the geometric confinement and the electric field are determinant for the existence of bound excited states in these structures.